2012
DOI: 10.1016/j.ijsu.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Is acupuncture beneficial in the treatment of Bell's palsy?

Abstract: A best evidence topic in facial nerve surgery was written according to a structured protocol. The question addressed was: in [patients with Bell's palsy], does [acupuncture] improve [facial nerve function and/or pain]? A total of 43 papers were identified using the reported search protocol, of which three articles represented the best available evidence to answer the clinical question. Two of these articles were review papers and together encompassed 13 primary articles. Publication details, type of study, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In China, acupuncture is frequently used to treat diseases and disorders of the nervous system such as stroke, dementia, Parkinson's disease, epilepsy, carpal tunnel syndrome, headache, and Bell's palsy [2]. Although some studies concluded that there is inadequate evidence to support the effectiveness of acupuncture for Bell's palsy [50, 51], a number of other studies have provided evidence that acupuncture is beneficial [2, 52, 53] or, as reported [54], that the efficacies of acupuncture, steroids, and natural course of recovery in Bell's palsy were the same with respect to the degree of recovery and speed of recovery. More importantly, Bell's palsy is a transient peripheral motor disease from which most of the patients would recover in several months and in which the brain anatomical structure was not significantly altered [55, 56].…”
Section: Introductionmentioning
confidence: 99%
“…In China, acupuncture is frequently used to treat diseases and disorders of the nervous system such as stroke, dementia, Parkinson's disease, epilepsy, carpal tunnel syndrome, headache, and Bell's palsy [2]. Although some studies concluded that there is inadequate evidence to support the effectiveness of acupuncture for Bell's palsy [50, 51], a number of other studies have provided evidence that acupuncture is beneficial [2, 52, 53] or, as reported [54], that the efficacies of acupuncture, steroids, and natural course of recovery in Bell's palsy were the same with respect to the degree of recovery and speed of recovery. More importantly, Bell's palsy is a transient peripheral motor disease from which most of the patients would recover in several months and in which the brain anatomical structure was not significantly altered [55, 56].…”
Section: Introductionmentioning
confidence: 99%
“…Cumberworth et al [ 60 ]. investigated evidence on the topic of acupuncture in patients with Bell’s palsy from 1948 to January 2012.…”
Section: Discussionmentioning
confidence: 99%
“…7-9 Liang et al 7 reported in 2006 that acupuncture and moxibustion exert a definite therapeutic effect on Bell palsy. In addition, Cumberworth et al, 8 in a Best Evidence Topic, reviewed the effectiveness of acupuncture in Bell palsy and concluded that the role and efficacy of acupuncture in Bell palsy should be considered unproven until well-designed clinical trials clearly show a benefit.…”
Section: Discussionmentioning
confidence: 99%